2014
DOI: 10.1159/000365813
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Ionized and Total Magnesium Levels in Pregnant Women with Gestational Diabetes Mellitus

Abstract: Background/Aims: The aim of this prospective study was to determine ionized and total magnesium (Mg) levels in pregnant subjects with and without gestational diabetes mellitus (GDM). Methods: Eighty-five women, 26-28 weeks pregnant, were recruited for routine oral glucose tolerance tests (OGTT); 45 had normal OGTT results and 40 were diagnosed with GDM. Electrolyte levels, including ionized and total Mg, were analyzed. Results: Gestational age and BMI were similar between the two groups (p = 0.800, p = 0.025).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…GDM insulin resistance and hyperinsulinemia may cause microvascular disease, resulting in the thickening of the basement membrane in capillary walls. This also contributes to the occurrence of maternal hypertensive disorders in pregnancy (26). In the present study, patients in the groups receiving high and medium doses of vitamin D supplementation were observed to display reduced insulin, HOMA-IR and total cholesterol levels.…”
Section: Discussionsupporting
confidence: 49%
“…GDM insulin resistance and hyperinsulinemia may cause microvascular disease, resulting in the thickening of the basement membrane in capillary walls. This also contributes to the occurrence of maternal hypertensive disorders in pregnancy (26). In the present study, patients in the groups receiving high and medium doses of vitamin D supplementation were observed to display reduced insulin, HOMA-IR and total cholesterol levels.…”
Section: Discussionsupporting
confidence: 49%
“…Changes in magnesium status in pregnant women may translate into effects on glucose metabolism, blood pressure, and the contractile response of uterine muscle. Thus, earlier reductions in maternal magnesium have been associated with an increased incidence of gestational diabetes [ 65 , 66 , 67 ] and may contribute to both preterm delivery and preeclampsia [ 36 , 68 , 69 ]. Few well-designed trials have examined the impact of dietary magnesium supplementation in pregnant women; thus, the benefits and risks of such remain controversial [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The low serum magnesium levels seen in the diabetic population may be a consequence of insulin resistance and dietary magnesium intake and intestinal hypo absorption may also be a factor in the low serum magnesium levels. Goker Tasdemir et al (2015) 16 found that there is no statistically significant difference in serum magnesium concentrations between healthy pregnant women and women with GDM.…”
Section: Discussionmentioning
confidence: 99%